THE EFFECT OF MARKETING MIX AND CUSTOMER VALUE ON CUSTOMER SATISFACTION AT UMKM TERAS KELAPA IN PADANG CITY - Dwi Fuji Wahyuni; Reci nurazira; Fanny Wulanda; Mega Putri Nolasary (Ikatan Dosen Menulis, 2025)
This study aims to determine the effect of marketing mix and customer value on customer satisfaction at UMKM Teras Kelapa and Bakso Solo Raya in Padang City. This research uses a descriptive quantitative method with purposive sampling technique involving 96 respondents. Data was collected using questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that both marketing mix and customer value had significant effects on customer satisfaction, either partially or simultaneously. The resulting regression model is Y = 5.301 + 0.360X1 + 0.365X2 + e. The coefficient of determination was 39%, while the remaining 61% is influenced by other factors not included in the model. The study emphasizes the importance of effective marketing strategies and the creation of customer value in enhancing customer satisfaction.